Exploring Approaches to Exercise Testing and Training in Adults with Cystic Fibrosis - Sawyer, Abbey (Curtin University, 2020)
This research involved a: (i) narrative review exploring the effects of high intensity interval training (HIIT) in people with chronic respiratory disease; (ii) survey of exercise testing and training procedures; (iii) randomised controlled trial (RCT) evaluating the effects of HIIT on exercise capacity in people with CF; (iv) systematic review mapping behaviour change techniques (BCTs) optimising participation in physical activity in young people with chronic cardiorespiratory conditions and; (v) evaluation of BCTs employed within the RCT.